Analysis of clinicopathological characteristics and prognostic factors of early‐stage human epidermal growth factor receptor 2 (HER2)‐low breast cancer: Compared with HER2‐0 breast cancer - Qian Wu; Fan Yang; YinHua Liu; Hong Zhang; Shuang Zhang; Ling Xin; Ling Xu (Cancer Medicine, 2023)
Abstract Purpose To investigate the clinicopathological characteristics and prognostic factors of early‐stage breast cancer (EBC) with human epidermal growth factor receptor 2 (HER2)‐low expression. Methods The clinicopathological data and follow‐up information of EBC patients with HER2‐low and HER2‐0 expression treated at the Breast Disease Center of Peking University First Hospital from January 2014 to December 2017 were analyzed. The prognosis between HER2‐low and HER2‐0 expression groups and with different hormone receptor (HR) expression were compared by statistics. Meanwhile, the expression of Ki67, androgen receptor (AR), TOPIIa, P53, PTEN, and CK5/6 were also analyzed with the HER2‐low expression and prognosis. Results Retrospectively analyzed 1253 cases of EBC, including 583 (46.5%) cases of HER2‐low breast cancer (BC) and 366 (29.2%) HER2‐0 BC cases. Among the HER2‐low BC patients, 487 (83.5%) were HR‐positive, while 96 (16.5%) were HR‐negative. Among the HER2‐0 BC patients, 265 (72.4%) were HR‐positive, while 101 (27.6%) were HR‐negative. Median follow‐up time was 53 months. The 5‐year disease‐free survival of HER2‐low BC patients was 90.2% (95% confidence interval [CI]: 87.2–93.1), and the 5‐year overall survival was 95.4% (95% CI: 93.3–97.6). Cox regression analysis showed that T stage, lymphovascular invasion, and/or perineural invasion were prognostic factors of HER2‐low BC patients. However, the 5‐year disease‐free survival and overall survival of patients in the HER2‐low and HER2‐0 groups were not significantly different in all patients, but a tendency of better prognosis in HER2‐low group was seen in HR‐negative tumors. Conclusion HER2‐low EBC patients accounted for 46.5% of the patient population. T stage, lymphovascular invasion, and/or perineural invasion were factors affecting the prognosis of BC patients with low HER2 expression. No significant difference in prognosis was noted between HER2‐low and HER2‐0 EBC patients. But in HR‐negative tumors, a tendency of better prognosis was seen in HER2‐low versus HER2‐0.